Prevalence and sociodemographic factors responsible for anaemia in pregnancy: experience in a military hospital in Bangladesh (BIRDEM Medical Journal, 2020)
Background: Anemia during pregnancy is associated with adverse outcomes. Prevalence of anemia is thought to be high in developing countries. This study was aimed at determining the prevalence and socio-demographic and reproductive factors associated with anemia among a group of pregnant mother.Methods: This cross-sectional observational study was conducted on pregnant women who visited the antenatal clinic of Combined Military Hospital (CMH), Savar, Dhaka from January 2017 to December 2019. Hemoglobin level was measured in all these women to assess the presence of anemia and was categorized according to the World Health Organization (WHO) criteria. Demographic data and information on maternal age, gestational age, educational and income level, and socioeconomic status were collected from anemic pregnant women and were analyzed.Results: Out of 1500 pregnant women 525 (35%) were found to be anemic (Hemoglobin